A new sol-gel route to prepare dense Al2O3 thin films. Issue 15 (15th November 2016) - Hu, Baofu; Jia, Erguang; Du, Baoli; Yin, Yuehong
Abstract: Anew sol-gel route has been applied to synthetize dense Al2 O3 thin films from aluminum isopropoxide (Al(OPri)3 )as raw precursor material. The results show that, in the solution, acetylacetone (AcAc) and aluminum form a complex compound which effectively suppresses the growth of colloidal particles and makes the sol very stable. Al2 O3 thin films fabricated by spin-coating method and calcined at 500 °C for 3 h possess an amorphous structure and exhibit a highly homogeneous surface texture without evidence of holes or cracks throughout the film. Moreover, the prepared films display a low leakage current and a high transmittance. This new sol-gel route appears to be a highly promising method to synthetize dense Al2 O3 thin films from Al(OPr i )3, and could provide a wide range of optical and electric applications.